Nitrogen affects the production and botanical composition in a grass/legume intercropped pasture (Revista de Ciências Agroveterinárias, 2008)
Nitrogen affects directly pasture production in grasses. However, there is lack of information about nitrogen effect on the performance of cool season grass/legumes intercropped pastures. The objective of this work was to evaluate the effect of two levels of nitrogen fertilization on the production and botanical composition of a pasture constituted by black oat + ryegrass + vetch + arrow leaf clover. The work was conducted in three sites, one in Canoinhas and two in Major Vieira, Santa Catarina State, southern Brazil, during 2006. Treatments were arranged in a randomized block design, with three replicates on each site. Two levels of nitrogen fertilization were evaluated: 0 and 100 kg ha-1. Nitrogen was applied when black had two tillers. The nitrogen rate of 100 kg ha-1 in pasture of black oat + ryegrass + vetch + arrow leaf clover increased forage production and grass participation in the botanical composition. There was an increase of vetch and arrow leaf clover contribution with the evolution of forage cycle.
Keywords: black oa; ryegrass; vetch; arrow leaf clover; competition.